2009
DOI: 10.1603/029.102.0512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reduced-Risk Insecticides on Soybean Aphid and Associated Natural Enemies

Abstract: Insect predators in North America suppress Aphis glycinesMatsumura (Hemiptera: Aphididae) populations; however, insecticides are required when populations reach economically damaging levels. Currently, insecticides used to manage A. glycines are broad-spectrum (pyrethroids and organophosphates), and probably reduce beneficial insect abundance in soybean, Glycine max (L.) Merr. Our goal was to determine whether insecticides considered reduced-risk by the Environmental Protection Agency could protect soybean yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
79
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 35 publications
11
79
0
2
Order By: Relevance
“…Such information could allow a better characterization of the exposure levels to thiamethoxam in the field and a more accurate characterization of risk of neonicotinoids to beneficial species in soybean crops. The results on the abundance of O. insidiosus in soybean fields with neonicotinoid seed treatments are consistent with the studies by Ohnesorg et al (2009) and Seagraves and Lundgren (2012), where no significant differences in O. insidiosus abundance were observed between fields derived from neonicotinoid treated and untreated fields. Orius insidiosus is a generalist predator consuming thrips, pollen, and nectar from flowers, vegetative tissue, and aphids in soybean fields (Rutledge and O'Neil 2005).…”
Section: Abundance Of O Insidiosus In Conventional Seed-treated Soybeansupporting
confidence: 90%
“…Such information could allow a better characterization of the exposure levels to thiamethoxam in the field and a more accurate characterization of risk of neonicotinoids to beneficial species in soybean crops. The results on the abundance of O. insidiosus in soybean fields with neonicotinoid seed treatments are consistent with the studies by Ohnesorg et al (2009) and Seagraves and Lundgren (2012), where no significant differences in O. insidiosus abundance were observed between fields derived from neonicotinoid treated and untreated fields. Orius insidiosus is a generalist predator consuming thrips, pollen, and nectar from flowers, vegetative tissue, and aphids in soybean fields (Rutledge and O'Neil 2005).…”
Section: Abundance Of O Insidiosus In Conventional Seed-treated Soybeansupporting
confidence: 90%
“…Broad-spectrum insecticides are the most commonly applied treatment for control of A. glycines (Olson et al 2008), and these insecticides negatively affect a wide range of insect taxa (Ohnesorg et al 2009). Application of insecticide to soybean Þelds likely will reduce selection for rotation-resistance in D. v. virgifera.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that the level of natural enemy induced mortality of the soybean aphid may be diminishing due to agricultural practices (Landis et al 2008, Ohnesorg et al 2009, Schmidt et al 2010. Olson et al (2008) reported that the most commonly used insecticides for control of soybean aphids in the Midwest included Asana, Lorsban, Mustang, and Warrior; all are considered broad-spectrum in nature and reduce natural enemy populations in addition to aphids (Ohnesorg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Olson et al (2008) reported that the most commonly used insecticides for control of soybean aphids in the Midwest included Asana, Lorsban, Mustang, and Warrior; all are considered broad-spectrum in nature and reduce natural enemy populations in addition to aphids (Ohnesorg et al 2009). The research presented here is the Þrst step in analyzing how our current soybean aphid management practices will respond to the changing soybean agricultural ecosystem in the midwestern United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation